Association between IGF-1 levels and MDD: a case-control and meta-analysis - Qiao, Xin; Yan, Jiaxin; Zang, Zongjun; Xi, Lei; Zhu, Wenli; Zhang, En; Wu, Lijuan (Frontiers in Psychiatry, 2024)
Purpose Insulin-like growth factor-1 (IGF-1) has a variety of neurotrophic effects, including neurogenesis, remyelination and synaptogenesis, and is an effective regulator of neuronal plasticity. Although multiple studies have investigated IGF-1 in depression-related disorders, few studies have focused on patients with a first episode of clearly diagnosed depression who had never used antidepressants before. Therefore, this study investigated first-episode and drug-naïve patients with depression to supplement the current evidence around IGF-1 levels in depressive disorders. Patients and methods This study consisted of two parts. In the first part, 60 patients with first-episode and drug-naïve depression and 60 controls matched for age, sex, and BMI were recruited from the outpatient department of the Fourth Hospital of Wuhu City, and the community. The case-control method was used to compare differences in serum IGF-1 levels between the two groups. In the second part, 13 case-control studies were screened through the database for meta-analysis to verify the reliability of the results. Results Results of the case-control study demonstrated that serum IGF-1 levels are significantly higher in patients with first-episode and drug-naïve depression compared to healthy controls (p<0.05), although there was no significant difference between men and women with diagnosed MDD, there was no significant correlation between serum IGF-1 level and age in patients with depression and no significant correlation between IGF-1 level and the severity of depression. The meta-analysis corroborates these findings and demonstrated that IGF-1 levels are significantly higher in MDD patients than in healthy controls. Conclusion Patients with first-episode and drug-naïve depression have higher IGF-1 levels, but the exclusion of confounding factors in studies of IGF-1 as it relates to depressive disorders must be taken into consideration strictly, and additional research is needed to fully understand the critical role of IGF-1 in depression. Systematic review registration PROSPERO, identifier CRD42023482222.